Spaces of escape: Sexuality in the age of the Internet. - Mahmoud, Miral A. (AUC Knowledge Fountain, 2018)
This thesis is an online ethnographic study of anonymous sexual interactions and expressions on the internet in twenty first century Egypt. I draw on how the internet is used as a space of freedom and resistance against the regulatory powers of state, society and religion, which decides how sexuality is expressed, discussed and practiced. I look at how a parallel sex culture is constructed online as opposed to the offline hegemonic, heteronormative sex culture. I observe sexual interactions and expressions in three anonymous internet platforms: an Egyptian chat room and two closed secret social media groups. I explore how alternative sexuality is represented, how men and women perceive their sexuality and how new modes of masculinity are performed. I look at how the anonymous online platforms are deemed sites of cultural production where Egyptians anonymously use it as a "safe" outlet to express their sexual dreams, fears, desires, orientations and behaviors without the fear of losing "face" in their offline lives. I attempt to understand a side of our truth in sex through analyzing the reciprocal relationship of our sexuality and the internet. Influenced by Foucault's work on sexuality, I examine how online sexual interactions and perceptions are subject to various changing forces such as internet anonymity, wide accessibility of information, and the availability of sexualized material. I look at how these forces shape the way sexuality is performed and perceived online. I draw on how the internet is used as an easy affordable, accessible, and anonymous sexual gratification vehicle in a country with suffocating economic and social circumstances. I look at how sex constitutes an integral part of their everyday experiences, fears, desires and dreams. This thesis is about how sex is practiced and expressed online in context of Egypt's strict regulatory powers of state, religion, and society and how in the process it was subject to other forces of change.